Three years follow up of open medial sub-talar dislocation of ankle: a case report - Siddharth, Arunodhaya; Gupta, Rahul; V., Sheshagiri; B. M., Pramod; Kumar, Shashi; A. J., Divya (International Journal of Research in Orthopaedics, 2023)
Open medial sub-talar dislocation is a rare lesion in traumatology. Even after early treatment, these injuries progress to sub-talar arthrosis. Here we describe a case of 24 years male with open type 3B medial sub-talar dislocation with calcaneum sustentaculum tali fracture following road traffic accident. He underwent emergency wound debridement and internal fixation with K-wires and VAC application. He was on regular monthly follow-up for 6 months and then 6 monthly follow-ups till date. K-wires were removed 8 weeks after surgery and gradual range of movement was started. Partial weight bearing was started at 12 weeks. He was pain free and returned to work after 8 months. At 3 years follow up patient is able to walk without pain, normal painless ROM at ankle. To the best of our knowledge, long term follow-up of patient with these lesions is not reported. Here we present a case with 3 years follow-up showing good results in patient with open sub-talar dislocation after early management with internal fixation with K-wires and VAC dressing.